Domestic Traumatism Among the Population and Children, Medical and Social Aspects (Texas Journal of Medical Science, 2022)
Domestic traumatism among the population and children remains one of the most important and urgent medical and social problems in all countries of the world, including the Republic of Uzbekistan. The study showed that in almost all countries of the world, including in our country, as well as in the Khorezm region, where the study is conducted, there is a tradition of increasing injuries among children in 2016-2020. In 2016, childhood injuries were 6.9% of the total incidence rate, up from 9.0% in 2020, and injuries increased slightly by just under 30%. In the region, 60.5% of child injuries were to boys and 39.5% were to girls, with the rate among boys being 1.53 times higher.